Breaking out: New freedoms in urban (re)design work by adding immersive environments. (June 2016) - Jutraž, Anja; Moine, Julie Le
Nowadays, urban planning and urban design are facing big changes in the use of different digital tools. Reaching out and engaging citizens and other stakeholders in urban design process are significant for good practice. Main problem discussed in this article is the lack of suitable tools/interfaces for instant collaboration between government, profession, and public. Article focuses on immersive environments, as full immersion could offer better notion of different proposals of urban design. As a case study, Immersive Terf is chosen; more exactly, article focuses on new approach and new development of tool Urban Redesign Terf. Deep immersive collaboration on design could free participant's mind and increase level of freedom in design/planning process. Immersive environments have already been used in building information modeling (BIM) managment, but innovation part, presented here, are technological: significant changes in the software and walk-through big models, which is the base for urban design and urban planning process.